SOSIALISASI IMPLEMENTASI KEBIJAKAN MUTU UNTUK PENINGKATAN KEPUASAN PELANGGAN DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Fithri Handayani Lubis; Selamat Ginting; Yunita Syahputri Damanik (INSTITUT KESEHATAN DELI HUSADA, 2021)
Policy implementation is transferring policies into programs and actions so that it requires various conditions related to the form of the problem to be solved by implementing the policy itself, environmental conditions that influence implementation, implementation organization and implementation resources and allocated resources. In addition to providing community health guidance, hospitals also have a main task in providing health services. Health services are services that have been carried out properly or not according to the community. The quality of health services must always be improved. One way to improve quality is to solicit feedback from the customer community or service users. To measure the level of customer satisfaction as service users and improve the quality of health services